Egg parasitoids of the corn leafhopper, Dalbulus maidis, in the southernmost area of its distribution range - Virla, Eduardo Gabriel (2013)
Egg parasitoids of the corn leafhopper, Dalbulus maidis (DeLong and Wolcott) (Hemiptera: Cicadellidae), were surveyed exposing sentinel eggs of the leafhopper along a latitudinal transect of 600 km in Argentina, the southernmost area of its distribution range. Four parasitoid species were obtained: the mymarids Anagrus breviphragma Soyka (Hymenoptera: Mymaridae), Anagrus flaveolus Waterhouse, and Polynema sp., and the trichogrammatid Pseudoligosita longifrangiata (Viggiani) (Hymenoptera: Trichogrammatidae). The low parasitism rate, low species richness, and high proportion of generalist egg parasitoids were quite clear in the southern distribution limit of the vector, in contrast to regions where corn crops are available all year round and there are continuous and overlapping generations of the pest. Further studies need to be done in order to determine the native host of the above egg parasitoids, the seasonal abundance, and the possible occurrence of other species affecting D. maidis populations in the studied area.